Structural And Psychological Empowerment on Work Behavior and Attitude of Nurse Educators in Selected Universities in Ilocos Norte - Sapinoso, Melody Luz; G. Aliswag, Emerson (Journal of Neonatal Surgery, 2025)
Background: Structural and psychological empowerment of nurse educators is essential to improve their professional development, job satisfaction, and pedagogical competence. Structural empowerment offers access to information, decision-making opportunities, and professional growth, whereas psychological empowerment generates autonomy, significance, and confidence in practice. In contrast, unempowerment may result in burnout, reduced job satisfaction, and turnover, with adverse effects on nursing education and patient outcomes. Filling the research gap on empowerment among nurse educators, especially in areas like Ilocos Norte, can guide focused interventions towards enhancing educational performance and the quality of health care. Methods: ​The study employed a descriptive correlational design to examine the relationships between structural empowerment, psychological empowerment, and work behaviors and attitudes among nurse educators in Ilocos Norte Result: The findings showed that the respondents had a high perception of transformational leadership, professional development, and mentorship as shown by their composite mean scores. Out of the three variables, professional development had the highest mean, implying that nurses are greatly motivated towards career and skill development. Mentorship also had a high score, which implies that the advice from experienced colleagues is important in their development. Transformational leadership attained the lowest but still high mean score, which indicates that despite of the leadership behaviors being acknowledged, they could have points for the improvement. Overall, there are indications that there is a positive and facilitative organizational environment where leadership, development, and mentoring are equally valued by nurses. Conclusion: The findings revealed that nurses generally perceive high levels of transformational leadership, professional growth, and mentorship, all of which are significantly and positively correlated. These results highlight the vital role of transformational leadership in enhancing mentorship and fostering professional development among registered nurses.